PELATIHAN PENULISAN KARYA ILMIAH PADA MAHASISWA SEMESTER V JURUSAN GIZI, POLITEKKES DEPKES GORONTALO - Ulfa Zakaria (Yayasan Education and Social Center, 2022)
Academic writing is an important aspect in the accumulation of student competency assessments. The final project that is the main requirement in completing studies at most universities in Indonesia is academic writing. In this regard, writing skills are the most basic needs for every student, both in the context of completing academic tasks during their studies and in supporting their existence as intellectuals in the wider community. The general problem in the preparation of academic writing lies in the ability to use scientific language appropriately along with the placement of all linguistic aspects to support the creation of academic writing that can be accepted by readers. This training is intended to help improve students' abilities in producing various forms of academic writing. After participating in a series of training activities carried out in the form of material debriefing, training, and evaluation, the trainees demonstrated adequate ability in terms of understanding the elements of an academic writing